Identification of a long-standing colony of Proechimys at the Instituto Evandro Chagas, Pará, Brazil, based on cytogenetic information - Ribeiro, Nelson Antonio Bailão (2011)
ABSTRACT The taxonomic classification of the genus Proechimys is complex because many of its species are morphologically similar but chromosomally different, with diploid (2n) values ranging from 14 to 62. The "Seção de Criação e Produção de Animais de Laboratório do Instituto Evandro Chagas" (The Division for Breeding and Production of Laboratory Animals, Instituto Evandro Chagas, Brazil) maintains a Proechimys colony for biomedical research. The colony members have been classified as P. guyannensis, which reportedly has 2n=40 and a fundamental number (FN) = 54. However, using karyotype analysis to aid in their taxonomic classification, we instead observed that a sample of the animals in this colony have 2n = 30 and FN = 56, with a medium-sized submetacentric X chromosome and a small acrocentric Y chromosome. Constitutive heterochromatin was distributed as follows: in the pericentromeric regions of chromosomes 6, 7, 9, 10, 11, 12, 13, 14 and X; on the distal short arms of chromosomes 3, 6, 10 and X; on the distal long arm of chromosome 12; on the long arm of the Y chromosome; and distally on both arms of chromosomes 7, 9 and 11. The nucleolar organizer regions (NORs) are located on the long arm of chromosome 9. This karyotype is consistent with that described previously for P. roberti, but not P. guyannensis, thus demonstrating the importance of using karyotyping for the taxonomic identification of Proechimys.